Combination of Value Stream Mapping and Vehicle Route Mapping: A Case Study of Internal Logistic Optimization - Immanuel, Evans (Jurnal Samudra Ekonomi dan Bisnis, 2025)
This study offers a solution to improve internal logistics efficiency, particularly trucking activities between buildings in a manufacturing environment. It applies three methods, that is Value Stream Mapping (VSM) to eliminate non-value-added (NVA) activities and reduce truck usage time, Capacity Analysis to optimize truck fill rates and minimize the total number of trips, as well as Vehicle Route Mapping (VRM) to select the shortest route and reduce travel time. As a result, PT. Sumarna reduced its internal trucks from 10 to 5 units, achieving a 47.15 percent of cost efficiency. The study is limited to internal trucking for goods with uniform dimensions and long shelf life, excluding volume fluctuations. This research highlights the effectiveness of combining VSM and VRM in internal logistics and serves as a benchmark for similar manufacturing settings that require internal transport between distributed buildings.